아일랜드, 농업개황 - 김용렬 (한국농촌경제연구원, 2007)
아일랜드는 우리나라와 같이 국토가 좁고 IT분야에서 최근의 급속한 발전을 이룬 나라이다. 아일랜드는 압축성장에 따른 지역간 불균형이 존재하고 남북분단에 따른 협력도 원활히 이루어지고 있어 우리에게 시사하는 바가 크다. 참고문헌 Central Statistics Office, http://www.cso.ie/ Department of Agriculture and Food, 2006, Annual Review & Outlook For Agruiculture & Food 2005/2006. -----, 2006, Ireland Rural Development National Strategy Plan 2007-2013(Draft). -----, 2006, Fact Sheet on Irish Agriculture. Department of Agriculture and Food 홈페이지 http://www.agriculture.gov.ie Rural Economic Research Center 홈페이지 http://www.tnet.teagasc.ie/rerc/ Teagasc 홈페이지 http://www.teagasc.ie/